2008
DOI: 10.2143/ac.63.5.2033228
|View full text |Cite
|
Sign up to set email alerts
|

New index of regional arterial stiffness assessed by tissue Doppler imaging

Abstract: Strain rate on the ascending aortic wall is a novel and more accurate index of regional arterial stiffness than brachial-ankle pulse wave velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We have previously shown that the assessment of these parameters is particularly relevant in the follow-up of patients with Marfan syndrome16 because aortic dissection may occur in the absence of marked aortic root dilatation, and in patients with aortic coarctation24 because ascending aorta distensibility may be reduced even after surgical repair. Positive results validating TDI assessment of arterial wall properties have also been obtained in the evaluation of abdominal aorta disease25 26 and characterisation of common carotid artery and aortic stiffness6 27 28 in normal adults.…”
Section: Discussionmentioning
confidence: 72%
“…We have previously shown that the assessment of these parameters is particularly relevant in the follow-up of patients with Marfan syndrome16 because aortic dissection may occur in the absence of marked aortic root dilatation, and in patients with aortic coarctation24 because ascending aorta distensibility may be reduced even after surgical repair. Positive results validating TDI assessment of arterial wall properties have also been obtained in the evaluation of abdominal aorta disease25 26 and characterisation of common carotid artery and aortic stiffness6 27 28 in normal adults.…”
Section: Discussionmentioning
confidence: 72%